Silent mutations in the Escherichia coli ompA leader peptide region strongly affect transcription and translation in vivo. - Deana, A (1998)
In order to test the effect of silent mutations on the regulation of gene expression, we monitored several steps of transcription and translation of the ompA gene in vivo , in which some or all codons between codons 6 and 14, frequently used in Escherichia coli , had been exchanged for infrequent synonymous codons. Northern blot analysis revealed an up to 4-fold reduction in the half-life of the mutated messengers and a >10-fold reduction in their steady-state amounts. Western blot analysis showed a 10-fold reduction in the amount of OmpA protein. Use of a system expressing a Rho-specific anti-terminator allowed us to detect a strong transcription polarity effect in the silent mutants. These results demonstrate that silent mutations can severely inhibit several steps of gene expression in E. coli and that code degeneracy is efficiently exploited in this species for setting signals for gene control and regulation.